The relationship between preschool teachers’ teaching experience and belief and their usage of ICT and the Internet in early childhood education - Jiale Lee (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
The Malaysian Government has put effort into Information and Communications Technology (ICT) for educational purposes encompassing the preschool setting. Regardless of the benefits of ICT to children’s learning development and the purpose of advocate integration of ICT in the education field, the usage of ICT by preschool teachers in the classroom was still not significant. The objective of this study was to examine the relationship between preschool teachers’ teaching experience and beliefs and their usage of (ICT) and the Internet in early childhood education (ECE). Results showed that there was no significant relationship between preschool teachers’ teaching experience and beliefs and their usage of ICT and the Internet in ECE. The findings recommend the policymakers to supply more ICT facilities for teachers to well integrate ICT and expose children to Virtual Learning Environments (VLEs)